Ester-based drilling fluids toward improved filtration properties performance - Kamis, Azmi; Ismail, Abdul Razak; Ismail, Issham; Khor, Siak Foo (Faculty of Engineering, UKM, 2000)
Synthetic based drilling fluids have been developed to meet difficult drilling targets with reduced environmental impact. Vegetables oils have been extensively studied as an alternative to common oil-based drilling fluids. However most of the vegetables oils are chemically reactive and can undergo alkaline hydrolysis at high temperature, which will increase the thickness of the filter cake and the filtrates loss volume. The development of an ester-base drilling fluid system with low filtration loss volume is the central focus of this research. It was found that Malaysian palm oil derivate could be used for the formulation of a suitable drilling fluid, which performed acceptable rheological properties compared to commercially available drilling fluid system. Under similar formulation, isopropyl laureate (IPL) demonstrated an acceptable low permeability filter cake and less filtrate loss volume compared to methyl laureate (ML). result showed that filtrate loss property can be further enhanced by increasing the quantity of fluid loss control agent as well as reducing the water content in the emulsion system.